2022
DOI: 10.3390/cancers14051167
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of FLASH-RT for Pancreatic Cancer

Abstract: Recent preclinical evidence has shown that ionizing radiation given at an ultra-high dose rate (UHDR), also known as FLASH radiation therapy (FLASH-RT), can selectively reduce radiation injury to normal tissue while remaining isoeffective to conventional radiation therapy (CONV-RT) with respect to tumor killing. Unresectable pancreatic cancer is challenging to control without ablative doses of radiation, but this is difficult to achieve without significant gastrointestinal toxicity. In this review article, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 66 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…One method of accomplishing this is the ultra‐rapid delivery of RT (FLASH RT: mean dose rates ≥40 Gy/s for a total duration of <200 ms 3 , 4 ), which has been shown to spare normal tissues and organs selectively while maintaining a tumoricidal effect in in vivo preclinical models. 4 , 5 , 6 , 7 , 8 This phenomenon has been called the “FLASH effect.” FLASH RT represents a fundamentally new paradigm for increasing the therapeutic index of RT relative to the same doses given at conventional (CONV) dose rates (0.01–0.1 Gy/s). 3 , 9 The ability to deliver the prescribed dose of radiation to a patient in a shorter overall treatment period with greater normal tissue sparing has enormous implications for the field of RT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One method of accomplishing this is the ultra‐rapid delivery of RT (FLASH RT: mean dose rates ≥40 Gy/s for a total duration of <200 ms 3 , 4 ), which has been shown to spare normal tissues and organs selectively while maintaining a tumoricidal effect in in vivo preclinical models. 4 , 5 , 6 , 7 , 8 This phenomenon has been called the “FLASH effect.” FLASH RT represents a fundamentally new paradigm for increasing the therapeutic index of RT relative to the same doses given at conventional (CONV) dose rates (0.01–0.1 Gy/s). 3 , 9 The ability to deliver the prescribed dose of radiation to a patient in a shorter overall treatment period with greater normal tissue sparing has enormous implications for the field of RT.…”
Section: Introductionmentioning
confidence: 99%
“…The main purpose of RT is to maximize the therapeutic gain in curing disease while minimizing any associated normal‐tissue complications. One method of accomplishing this is the ultra‐rapid delivery of RT (FLASH RT: mean dose rates ≥40 Gy/s for a total duration of <200 ms 3,4 ), which has been shown to spare normal tissues and organs selectively while maintaining a tumoricidal effect in in vivo preclinical models 4–8 . This phenomenon has been called the “FLASH effect.” FLASH RT represents a fundamentally new paradigm for increasing the therapeutic index of RT relative to the same doses given at conventional (CONV) dose rates (0.01–0.1 Gy/s) 3,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence suggests that FLASH RT spares normal tissues to a greater extent than CONV RT while maintaining iso-effectiveness in terms of tumor control [ 1 , 3 , 4 ]. This so-called “FLASH effect” has been demonstrated in a variety of animal models and organ systems [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The full potential of radiation therapy (RT) as a cancer therapy is limited by its toxicity to normal tissue structures, especially critical structures adjacent to the treatment site. Preclinical data have indicated that delivering radiation at dose rates of 40 Gy/s or higher over a period less than 200 ms, commonly referred to as ultra‐high dose rate (UHDR) irradiation, has been shown to have the radiobiological advantage of selectively sparing normal tissue while maintaining a tumoricidal effect in in vivo preclinical models, which has been dubbed the FLASH effect 1–5 . Although the FLASH effect has been observed in many organ systems, the physical characteristics of the radiation beam such as dose per pulse (DPP), pulse repetition frequency (PRF), pulse width (PW), mean dose rate, and instantaneous dose rate needed to achieve and optimize the FLASH effect are still largely unknown 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical data have indicated that delivering radiation at dose rates of 40 Gy/s or higher over a period less than 200 ms, commonly referred to as ultrahigh dose rate (UHDR) irradiation, has been shown to have the radiobiological advantage of selectively sparing normal tissue while maintaining a tumoricidal effect in in vivo preclinical models, which has been dubbed the FLASH effect. [1][2][3][4][5] Although the FLASH effect has been observed in many organ systems, the physical characteristics of the radiation beam such as dose per pulse (DPP), pulse repetition frequency (PRF), pulse width (PW), mean dose rate, and instantaneous dose rate needed to achieve and optimize the FLASH effect are still largely unknown. 6,7 Difficulties in measuring these irradiation parameters with conventional detectors and measurement techniques have led to underreporting and inconsistencies in the published literature.…”
Section: Introductionmentioning
confidence: 99%